Editorial - Clavijo, Amparo (Colombian Applied Linguistics Journal, 2008)
Welcome to the tenth edition of the Colombian Applied Linguistics Journal. This year we are celebrating ten years of our publication and I would like to thank all the authors who have contributed with research, theoretical and pedagogical articles in the fields of ELT and Applied Linguistics during this time. I also want to thank all my colleagues in the editorial advisory board for evaluating the articles with rigour, commitment and dedication and the journal assistants for helping make our publication a reality every year.